Persebaran Tingkat Kebisingan Akibat Kegiatan Operasional Mesin Produksi Minuman Kemasan PT X di Daerah Pasuruan - Tuhu Agung Rachmanto; Nurilita Amalia Cahyani (Prosiding ESEC, 2023)
PT X is a company engaged in the bottled water and soft drink industry where the production machines that are operated cause noise pollution which pollutes the environment around industrial settlements. Based on the known environmental impacts from the operational activities of one of the bottled water and soft drink industries in the Pasuruan area, noise levels, noise distribution, as well as solutions and anticipatory actions as a result of noise disturbances caused by industrial activities can be identified. In an effort to determine the impact of noise on the area around the business location, mapping is carried out using Surfer v16.0 software so that the contour map and the distribution of areas affected by the spread of industrial noise pollution are known. The analytical method used is to collect data in the production area or space as well as the area around industrial activities. The largest noise measurement results were in the production area of 83,9 dB(A) and the closest residential area II had the smallest noise level of 23,7 dB(A) as measured using a Sound Level Meter (SLM).